Cancellation of the Deed of Statement of Decision of the GMS of PT Based on the Decision of the Kendari District Court (Number 83/Pdt.G/2020/Pn Kdi) - Septiarni Marsang, Ni Dya; Hafidz, Jawade (Jurnal Konstatering, 2025)
Abstract. This study aims to determine and analyze the basis for the judge's considerations in decision number 83/Pdt.G/2020/PN. Kdi, to determine and analyze the validity of the deed of statement of decision of the extraordinary general meeting of shareholders of a limited liability company based on the decision of the Kendari District Court number 83/Pdt.G/2020/PN. Kdi, to determine and analyze the notary's responsibility for the cancellation of the deed of statement of decision of the extraordinary general meeting of shareholders of a limited liability company based on the decision of the Kendari District Court number 83/Pdt.G/2020/PN. Kdi. The approach method in this study is the statute approach. This type of research is a normative juridical research. The types and sources of data in this study are secondary data obtained through literature studies. The analysis in this study is perspective. The results of this study indicate that they have never received an invitation to attend the EGMS and have not given power of attorney to other parties to represent them in attending the EGMS. The cancellation is also based on the provisions of Article 79 paragraph (2) and paragraph (3) of the PT Law, as well as the existence of unlawful acts (Onrechtmatige Daad) committed by the defendants and co-defendants which caused losses to the plaintiffs, in accordance with Article 1365 of the Civil Code. The holding of the EGMS of PT Tomia Mitra Sejahtera by Defendant 1 is considered invalid because it is contrary to the provisions stipulated in the Limited Liability Company Law (UUPT) and contains legal defects in its implementation. The actions of the Co-Defendant, in this case the notary, are considered unlawful acts by the court decision which fulfills the elements of Article 1365 of the Civil Code, which causes losses to the Plaintiff. However, in the decision, the notary is not charged with paying compensation because in making the Deed of Statement of Decisions of the Company's General Meeting of Shareholders, the notary is only responsible for the formal form of the deed, considering that the notary was not present in person at the GMS. Therefore, the notary is not responsible for the contents contained in the deed. The validity of the material or contents of the deed is the responsibility of the party organizing the EGMS and making decisions at the meeting, namely Defendant 1.Keywords: Cancellation; Company; Liability; Limited.